PENGARUH PEMBELAJARAN ECOPRINT BERBASIS OPEN-ENDED PLAY TERHADAP PERKEMBANGAN KREATIVITAS ANAK DI TAMAN KANAK-KANAK - Haysa; Asdi Wirman (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Low levels of creativity among early childhood students are caused by a learning approach that remains teacher-centered and fails to provide children with sufficient opportunities to explore and express their ideas freely. One alternative learning approach that can be implemented is ecoprinting based on open-ended play, which utilizes natural materials and gives children the freedom to create. This study aims to determine the effect of open-ended play-based ecoprint learning on the creativity of 5–6-year-old children at Aisyiyah Bustanul Athfal Sungai Buluah Kindergarten, Agam Regency. The study employed a quantitative approach using a pre-experimental method and a one-group pretest-posttest design. The study sample consisted of 13 children, including 6 boys and 7 girls. Data were collected using an observation sheet containing six indicators of creativity and analyzed using descriptive statistics and a paired-sample t-test. The research results show that the children’s average creativity score increased from 10.54 on the pretest to 19.92 on the posttest. The hypothesis test results show a significance value of 0.000 < 0.05, indicating a significant difference between the pretest and posttest scores. These findings indicate that ecoprint learning based on open-ended play has a significant effect on enhancing the creativity of children aged 5–6 years. This activity provides children with opportunities to explore, solve problems, and produce diverse works using natural materials, making it an effective alternative learning activity for developing creativity in early childhood.